Ligamentization of the reconstructed ACL differs between the intraarticular and intraosseous regions: A quantitative assessment using UTE-T2* mapping. - Rikuto Yoshimizu; Junsuke Nakase; Miho Okuda; Kazuki Asai; Mitsuhiro Kimura; Tomoyuki Kanayama; Yusuke Yanatori; Hiroyuki Tsuchiya (PLoS ONE)
Background The purpose of this study was to prospectively observe the trends of ultrashort echo time (UTE)-T2* values for the intraarticular and intraosseous regions of reconstructed anterior cruciate ligaments from 6 to 12 months after anterior cruciate ligament reconstruction by using UTE-T2* mapping, and to investigate the changes and differences over time in each region. Methods Ten patients underwent UTE-T2* mapping of the operated knee at 6, 9, and 12 months after anterior cruciate ligament reconstruction. The UTE-T2* values of intraarticular and intraosseous regions of reconstructed anterior cruciate ligaments at 6, 9, and 12 months postoperatively were statistically compared. Results The UTE-T2* values of the intraarticular region at 6 months postoperatively were significantly higher than those at 9 and 12 months. There were no significant differences in the UTE-T2* values at 6, 9, and 12 months postoperatively in the intraosseous region. At 6 months postoperatively, the UTE-T2* values of the intraarticular region were significantly higher than those of the intraosseous region. The UTE-T2* values of the intraosseous region at the tibia were significantly lower than those of the other sites at any postoperative time point. Conclusions According to UTE-T2*mapping-based findings, histological maturation of reconstructed ACLs is faster in the intraosseous region than in the intraarticular region. In particular, the intraarticular region is still undergoing rapid histologic changes at 6 months postoperatively, and its tissue structure is less substantial than normal. The findings of this study may provide clues to determine the optimal timing for safe return to sports in terms of ligamentaization of reconstructed ACLs.